2022
DOI: 10.1111/sjop.12802
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in emotional reminiscing in a Scandinavian sample

Abstract: Emotional reminiscing is a context where children learn culture‐specific ways of understanding past emotional experiences through parentally scaffolded conversations, and learn how to connect these disparate experiences into their developing autobiographical memory. The goal of the present investigation was to explore possible gender differences in emotional reminiscing in an egalitarian cultural context (Denmark). Mothers and fathers from families (N = 88) reminisced about a happy and a sad past event with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Yet, some studies did not claim gender differences in mother-child reminiscing. For instance, Svane et al (2022) explored the gender differences in emotional memory conversations, and they did not find significant results neither for the parent's gender nor for the child's gender. However, the gender ideology of the parents and the cultural context may have mattered in finding nonsignificant results since they conducted the study with a sample of Danish citizens of a mainly egalitarian culture.…”
Section: Child's Gender and Its Effect On Mother-child Reminiscingmentioning
confidence: 96%
See 1 more Smart Citation
“…Yet, some studies did not claim gender differences in mother-child reminiscing. For instance, Svane et al (2022) explored the gender differences in emotional memory conversations, and they did not find significant results neither for the parent's gender nor for the child's gender. However, the gender ideology of the parents and the cultural context may have mattered in finding nonsignificant results since they conducted the study with a sample of Danish citizens of a mainly egalitarian culture.…”
Section: Child's Gender and Its Effect On Mother-child Reminiscingmentioning
confidence: 96%
“…In several studies, female children were found to have an advantage over boys regarding the total word usage and the intensity of emotional expression in the reminiscing context due to the differential socialization process imposed by their parents. However, some studies failed to indicate such gender differences, as well (e.g., Svane et al, 2022). Therefore, gender differences in the reminiscing context should be further investigated to clarify this issue.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, it would be more inclusive to reveal studies examining gender differences in language on both the content and the linguistic level. Current literature does not generally encompass both; some studies focused on gender differences only on the linguistic level (Lange & Zaretsky, 2021), and some other studies demonstrated gender differences only in emotional content (Svane et al, 2022). To reach a more precise and more generalizable conclusion about gender differences in language, either linguistic variables or content variables such as emotional expression, all studies should be summarized, and a conclusion should be drawn based on the findings.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Especially cultural characteristics would matter regarding whether parents internalize egalitarian or traditional gender ideology when transferring the emotional socialization process to their children. This is because parents with a more egalitarian gender view are less likely to consider the child's gender when interacting and teaching emotional expression (Svane et al, 2022). Traditional families, on the other hand, would consider the child's gender and interact accordingly.…”
Section: Theoretical Background Of Gender Differences In Languagementioning
confidence: 99%